Is the PBL (Problem Based Learning) applicable for the discipline of Dental Radiology? A systematic review (Research, Society and Development, 2021)
The aim of this study was to verify, through a systematic review, whether the active methodology of PBL (Problem Based Learning) is applicable for teaching the discipline of Dental Radiology. This review was carried out following the guidelines of PRISMA-P, using the PICO strategy to implement the eligibility criteria, seeking to answer the following question: “The PBL (Problem Based Learning) is applicable for the discipline of Dental Radiology?”. A systematic review was carried out in the PubMed databases (including MedLine), SciELO, LILACS, Web of Science and IEEE Xplore, as well as a search in gray literature in the electronic platforms, OpenThesis and Open Access Thesis and Dissertations, in addition to the manual search for cross-references of original articles. In addition, the Bollean operators, AND and OR were used, combined with the descriptors, these selected using the Descriptors in Health Science (DeCS) and Medical Subject Headings (MeSH), to enhance the search strategy. The selection of studies was performed by two reviewers and eligibility criteria were adopted for the selected works. The PBL proved to be a teaching methodology that brings benefits for the training of dental surgeons capable of dealing with daily situations, being a viable and applicable alternative for the discipline of dental radiology. However, due to the uncertainties found in the studies those included, evidenced by the high risk of bias, further research should be carried out to reduce such knowledge gaps about the best method in the teaching-learning process.